Implementasi Layanan Bimbingan dan Konseling dalam Mengatasi Kenakalan Remaja melalui Konseling Kelompok - Juwita Madira; Saniya Putri Ayu Febiolantika; Risma Anita Puriani (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
Juvenile delinquency in schools, including behaviors like failure to follow rules, lack of discipline, and aggression, significantly impacts students' academic and social development. This behavior often indicates underlying issues that require effective intervention. Group counseling, as part of guidance and counseling services, plays a crucial role in addressing these problems by helping students develop self-control, emotional regulation, and healthy social interactions. The purpose of this study is to explore how guidance and counseling services can be used to mitigate juvenile delinquency in schools. The study involves a comprehensive review of relevant literature, including books and articles on group counseling, behaviorist approaches, and cognitive behavioral therapy. The findings suggest that techniques such as positive reinforcement, the promotion of good behavior, managing triggers, and altering thought patterns are effective strategies in helping students reduce inappropriate actions. These interventions can lead to improved discipline, better relationships with peers, and enhanced self-awareness. However, the success of these counseling services is contingent on the support from school leadership, the active involvement of guidance and counseling teachers, and the overall school environment. This study emphasizes the importance of a holistic approach to address juvenile delinquency and foster positive behavioral change in students.